Comparison of the radius of curvature in the cams which used in the displacement law beziér curves and cyclic and harmonic curves (2018)
The work shows the radius of curvature for different variations of the angle of rotation β and of the ratio of Ro/L, the study is shown for the case in which the laws of displacement of the cams have been designed by Bézier curves and these results are compared with those obtained by harmonic and cyclic curves.